Os impactos de efeito dominó causados em outros clientes pela exposição ao comportamento disfuncional do cliente - Telli, Denise Garcia (2016)
This study sought to evaluate the reaction of other customers exposed to dysfunctional customer behavior in the context of services, moreover the impact of the acceptability of dysfunctional behavior over this reaction and the moderation of ethics and risk perception. There are no empirical studies on the relationship between exposure to dysfunctional customer behavior and the variables: acceptability, ethics, risk perception and the domino effect thus these objectives are interesting to marketing academics. To achieve the objectives, two experimental studies were performed with an online sample (n = 190). It was shown that the acceptability of the dysfunctional behavior as the individual ethical level impact the relationship between exposure to dysfunctional customer behavior and the likelihood of domino effect. The perception of risk directly impacts the likelihood of domino effect when the individual evaluates the behavior of another person. But when the individual evaluates his own behavior intention, the perception of risk impacts the domino effect only when associated with the acceptability of the dysfunctional customer behavior. For service managers these results are relevant because they demonstrate that consumers "learn" with others, therefore companies should emphasize to consumers how dysfunctional behaviors are unacceptable, pursuing to minimize the losses from dysfunctional customer behavior.